A Self‐Degradable Conjugated Polymer for Photodynamic Therapy with Reliable Postoperative Safety. Issue 4 (13th December 2021) - Huang, Hongye; Xie, Wensheng; Wan, Qing; Mao, Liucheng; Hu, Danning; Sun, Hua; Zhang, Xiaoyong; Wei, Yen
Abstract: As a noninvasive therapeutic technique, photodynamic therapy (PDT) has attracted numerous research interests for cancer therapy. Nevertheless, the residual photosensitizers (PSs) still produce reactive oxygen species (ROS) and damage normal cells under sunlight after PDT, which limits their practical application in clinic. Herein, the authors propose a self‐degradable type‐I PS based on conjugated polymer, which is composed of aggregation‐induced emission (AIE) and imidazole units. Due to the effective conjugated skeleton and unique AIE properties, thus‐obtained polymers can effectively generate superoxide radical (O2 − ) through the type‐I process under light irradiation, which is ideal for hypoxic tumors treatment. Intriguingly, under light irradiation, O2 − produced by the conjugated polymers can further lead to the self‐degradation of the polymer to form nontoxic micro‐molecules. It not only helps to resolve the potential phototoxicity problems of residual PSs, but also can accelerate the metabolism of the conjugated polymers to avoid the potential biotoxicity of drug accumulation. This work develops a self‐degradable type‐I PS, which can turn off the generation of ROS in time after PDT, providing a novel strategy to balance the PDT effect and postoperative safety. Abstract : A self‐degradable type‐I photosensitizer is developed based on conjugated polymer. Conjugated polymers can effectively produce O2 − under light irradiation, which is ideal for hypoxic tumors treatment. Meanwhile, the generated O2 − can in return degrade the polymer to form biocompatible micro‐molecules. Significantly, this self‐degradable conjugated polymer provides a novel strategy to balance the PDT effect and postoperative safety.